2019
DOI: 10.1371/journal.pone.0209982
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the major QTL for seed coat color in Brassica rapa var. Yellow Sarson by use of NIL populations and transcriptome sequencing for identification of the candidate genes

Abstract: Yellow seed is a desirable trait in Brassica oilseed crops. The B. rapa var. Yellow Sarson carry unique yellow seed color genes which are not only important for the development of yellow-seeded oilseed B. rapa cultivars but this variant can also be used to develop yellow-seeded B. napus. In this study, we developed near-isogenic lines (NILs) of Yellow Sarson for the major seed coat color QTL SCA9-2 of the chromosome A9 and used the NILs to fine map this QTL region and to identify the candidate genes through li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…A strong association peak was also detected on chromosome A3 for a simple categorical seed colour trait (Figure S6). In this case, using the SNP with the strongest association with this trait, Cab016066.1:252:G, we were able to assign the correct seed colour of individuals in the test panel with 79% accuracy, contributing an additional locus to the seed colour QTL already reported in Brassica species (Wang et al, 2017;Zhao et al, 2019;Zhang et al, 2019).…”
Section: Associative Transcriptomicsmentioning
confidence: 70%
“…A strong association peak was also detected on chromosome A3 for a simple categorical seed colour trait (Figure S6). In this case, using the SNP with the strongest association with this trait, Cab016066.1:252:G, we were able to assign the correct seed colour of individuals in the test panel with 79% accuracy, contributing an additional locus to the seed colour QTL already reported in Brassica species (Wang et al, 2017;Zhao et al, 2019;Zhang et al, 2019).…”
Section: Associative Transcriptomicsmentioning
confidence: 70%
“…Functional characterization of the WS-induced candidate genes is required to further identify candidate genes controlling waterlogging-tolerant traits. Additionally, recent studies demonstrated that differentially-regulated genes controlling for the traits of interest could be accurately identified using comparative transcriptome RNA-seq analysis of near-isogenic lines (NILs) [66,67]. Clearly, this method could help to narrow down the list of candidate genes responsible for waterlogging tolerance in zombi pea by removing genetic background effects.…”
Section: Discussionmentioning
confidence: 99%
“…Yu (2013) reviewed the molecular mechanism of manupulating seed coat color in Brassica species, including the homologous TTs cloned in Brassicas [20]. Besides, molecular markers have also been developed for yellow-seeded B. rapa [21][22][23], B. juncea [24,25] and B. napus. Liu et al (2012) reported a lignin biosynthesis gene, BnCCR1, associated with yellow seed character, indicating a strong correlation between seed color and lignin content [26].…”
Section: Introductionmentioning
confidence: 99%